1996
DOI: 10.1002/eji.1830260143
|View full text |Cite
|
Sign up to set email alerts
|

Early development and progression of lymphocyte‐stimulatory cross‐reactive idiotypes expressed on antibodies to soluble egg antigens during Schistosoma mansoni infection of mice

Abstract: Idiotypes (Id) that stimulate immunoregulatory anti-Id T lymphocyte proliferation are expressed on murine and human antibodies (Ab) to soluble egg antigens (SEA) of Schistosoma mansoni. Kinetics of early expression of these stimulatory Id have now been studied using immunoaffinity-purified serum anti-SEA Ab from mice infected with S. mansoni for 6, 7, 8, 12, or 16 weeks. Rabbit anti-Id Ab specific for mouse anti-SEA Id expressed at 8 weeks post-infection (anti-8WkId) demonstrated the strongest interactions wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1997
1997
2003
2003

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Although we have reported that CRI can be detected early in S. mansoni infections (21), our previous longitudinal studies of MSS and HSS mice suggested that differences between pathologic groups occurred later in infection as significant differences between anemia and serum triglyceride levels in mice that develop these distinct pathologies are not detected until 10 and 14 wk after infection, respectively (26). The current data indicate that the immunobiologic processes that determine whether or not experimental animals in this model develop severe pathology are in place very early in infection, concurrent with worm maturation and egg production.…”
Section: Resultsmentioning
confidence: 80%
“…Although we have reported that CRI can be detected early in S. mansoni infections (21), our previous longitudinal studies of MSS and HSS mice suggested that differences between pathologic groups occurred later in infection as significant differences between anemia and serum triglyceride levels in mice that develop these distinct pathologies are not detected until 10 and 14 wk after infection, respectively (26). The current data indicate that the immunobiologic processes that determine whether or not experimental animals in this model develop severe pathology are in place very early in infection, concurrent with worm maturation and egg production.…”
Section: Resultsmentioning
confidence: 80%
“…Soluble extracts of SEA or SWA have been used to study immune responses to S. mansoni [15][16][17]. To establish whether antigens within these extracts are able to influence the development of diabetes, groups of 4-week-old female NOD mice were injected once a week for 15 weeks with 50 ?…”
Section: Soluble Worm or Egg Antigens From S Mansoni Prevent Diabetementioning
confidence: 99%
“…The ability of spleen cells to proliferate in vitro was measured as previously described (Bosshardt, Nix & Colley 1996). Briefly, single cell suspensions were prepared from the spleens of uninfected mice, or mice with S. mansoni infections of eight weeks (acute) or 20-25 weeks (chronic).…”
Section: Lymphocyte Proliferationmentioning
confidence: 99%